Role of susceptibility weighted imaging in characterization of intra-cranial lesions - Sahdev, Ravinder; Rao, Akhilesh; Yadu, Neha; Shukla, Y (International Journal of Medical Research and Review, 2016)
Background: Intrinsic differences between magnetic susceptibility of tissues can be used to generate a unique type of contrast in Magnetic Resonance Imaging (MRI), particularly to characterize tissues and improve the sensitivity for certain lesions, most notably hemorrhagic foci or calcification. Methods: A blinded retrospective review of all brain imaging studies done at our centre between March 2014 and February 2016. One of them reviewed the MR images with exclusion of SWI, while the other radiologist reviewed the entire set of images including SWI. Their findings were then compared to study the efficacy of SWI in better detection and characterization of lesions. Results: The study included 3710 patients with different brain lesions. SWI revealed positive lesions in at least 619 of these patients. 21 patients with traumatic brain injury, 32 patients with cerebral microbleeds, 78 patients with brain tumors, 27 patients with venous malformations, 128 patients with intra-cranial calcifications, 277 patients with infarcts and 56 patients with extra-axial hemorrhage. Out of the 619 lesions, SWI played a significant role in lesion characterization in at least 198 patients which is about 5.33% of our total cohort of 3710 patients. Conclusion: SWI images are fast sequences requiring no more than a total scan time of about 3 minutes. Inclusion of this sequence as a part of brain pathology canplay an important role in diagnosing different brain lesions as well as avoiding missing hemorrhagic lesions thus aviding inappropriate therapeutic regimens with catastrophic results.